Mechanical behavior of Graphene decorated carbon fiber reinforced polymer composites: An assessment of the influence of functional groups. (July 2019) - Gangineni, Pavan Kumar; Yandrapu, Sagar; Ghosh, Sohan Kumar; Anand, Abhijeet; Prusty, Rajesh Kumar; Ray, Bankim Chandra
Abstract: Decoration of the Carbon fiber (CF) surface using graphene based nano-fillers (GBN) by the electrophoretic deposition (EPD) is possibly one of the most emerging techniques for the enhancement of the mechanical response of carbon fiber reinforced polymer (CFRP) composites. Present investigation is focused on enhancing the flexural and interlaminar properties of a CFRP composite by surface modification of carbon fiber by EPD technique using GBN (graphene (G), graphene oxide (G-O), graphene hydroxyl (G-OH) and graphene carboxyl (G-COOH)). The highest flexural strength and interlaminar shear strength was obtained for the G-COOH modified CFRP composite, which are 9.6% and 22.9% higher than that of control CFRP respectively. Dynamic mechanical thermal analysis (DMTA) was conducted in the temperature range of 30 °C to 180 °C to understand the temperature dependent mechanical behavior of all the composites. In addition, fractographic analysis was carried out using scanning electron microscopy (SEM) to understand various failure micro-mechanisms.